(untitled) (REMUNOM, 2026)
Brazilian poultry farming occupies a prominent position in the global production and commercial landscape, demanding increasingly efficient and sustainable systems aligned with animal welfare requirements. In this context, the incorporation of digital technologies has driven the modernization of production systems, especially through the concepts of Precision Livestock Farming, Big Data, the Internet of Things (IoT), and Artificial Intelligence. This study aimed to conduct a literature review on the main technologies applied to contemporary poultry farming, with an emphasis on the automation of production systems, environmental monitoring, bird welfare, and production efficiency. The review shows that the integrated use of sensors, automated systems, real-time data analysis, and intelligent algorithms allows for greater control of environmental parameters, optimization of feed management, reduction of waste, and improvement in the quality of poultry products. Furthermore, these technologies contribute to more assertive decision-making and reduced dependence on manual labor. However, despite the advances, challenges related to implementation costs, technical training, and connectivity in rural areas still limit the widespread adoption of these tools. In conclusion, digital technologies represent a promising path for strengthening modern poultry farming, being fundamental to ensuring the sector’s productivity, sustainability, and competitiveness.